Marketing Hospitality / Tom Powers - Tom, Powers
To say this book practices what it preaches would set very ambitious goals for a marketing text. Sitll, there is a strong element of marketing in the way the book is organized and presented. I have tried to do three things: to target a market, to meet customers' needs and wants, and to sell something an idea. That is not all there is to marketing, as the reader of this text should discover, but it does cover a lot of territory.